PENGARUH MASA KERJA DAN DISIPLIN TERHADAP PENERIMAAN JASA PELAYANAN (KAPITASI) PNS DI UPT. PUSKESMAS KECAMATAN UNTER IWES - K Kamaruddin; Ika Fitriyani; Dewi Intania Sofianita (Pusat Riset dan Publikasi, 2020)
The purpose of this study was to know whether there was a significant effect of the variables of working Period (X1) and discipline (X2) simultaneously and partially toward Service revenue Acceptance (Y) for civil servant (PNS) in Integrated Service Unit (UPT) of Unter Iwes . Type of this study was associative, which is research that aims to know the influence of independent variable toward dependent variable. The data used was secondary with data collection techniques using documentation. The analytical tool used in this study was classic assumption test, multiple linear regression test, t and F statistical tests, and the coefficient of determination (R2).The findings in this study showed that the working period variable did not have a significant effect toward Service acceptance revenue of civil servant (PNS) in Service Integrated Unit (UPT) of Unter Iwes, Unter Iwes sub-district while the discipline variable had a significant effect toward service revenue acceptance for civil servant (PNS) in integrated service unit (UPT) of Unter Iwes, Unter Iwes sub-district. Simultaneously, the Variables of working Period and Discipline had a significant effect toward Service revenue acceptance of civil servant (PNS) in integrated service unit (UPT) of Unter Iwes, Unter Iwes sub-district. The variable of working period and discipline affected the service acceptance revenue variable of 79.0 percent. This value proved that working Period, discipline and facilities had an influence toward Service revenue with a high level of correlation so that the relationship was very significant (meaningful), while its remaining of 21.0 percent was caused by other variables outside the scope of the study such as salary, performance, allowances and others.